2018
DOI: 10.1104/pp.18.00296
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Specific Interaction of NF-YC and CURLY LEAF during the Floral Transition Regulates Flowering

Abstract: The flowering time of higher plants is controlled by environmental cues and intrinsic signals. In Arabidopsis (), flowering is accelerated by exposure to long-day conditions via the key photoperiod-induced factor FLOWERING LOCUS T (FT). Nuclear Factor-Y subunit C (NF-YC) proteins function as important mediators of epigenetic marks in different plant developmental stages and play an important role in the regulation of transcription, but the mechanistic details of this remain unknown. In this study, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…This is likely the case, as we and others have shown that SVP represses flowering in a dosage-sensitive manner (Hartmann et al, 2000;Li et al, 2015). Of note, we and others have consistently found the up-regulation of FT in the clf-29 mutants (Farrona et al, 2011;Jiang et al, 2008;Liu et al, 2018). But, unlike the previous studies, we did not find significant CLF/SWN enrichment at this locus (Supporting Information Figure S10b).…”
Section: Discussioncontrasting
confidence: 64%
“…This is likely the case, as we and others have shown that SVP represses flowering in a dosage-sensitive manner (Hartmann et al, 2000;Li et al, 2015). Of note, we and others have consistently found the up-regulation of FT in the clf-29 mutants (Farrona et al, 2011;Jiang et al, 2008;Liu et al, 2018). But, unlike the previous studies, we did not find significant CLF/SWN enrichment at this locus (Supporting Information Figure S10b).…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, the Arabidopsis ABF proteins interact with each other (Yoshida et al, ). Specifically, Arabidopsis ABF3 and ABF4 regulate SOC1 expression, thereby affecting drought stress responses via interactions with NF‐YC (Hwang, Susila, Nasim, Jung, & Ahn, ), which is a key component that integrates GA and ABA signaling and regulates seed germination and flowering (Liu et al, ; Liu et al, ). In pear, ABF3 may function with other components to regulate the expression of downstream genes associated with dormancy transitions and other stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…There may be at least three reasons to explain this phenomenon: (i) Epigenetic mechanism. Previous evidence supported that the NF-Y transcription factor as important modulators of epigenetic marks controlling flowering [50][51][52][53] In summary, to elucidate the role of NF-Y transcription factor in poplar flowering induction and molecular regulation mechanism will be important for people to understand the role and function of NF-Y transcription factor family in woody plants, and provide important theoretical basis for regulating flowering time and shortening breeding cycle.…”
Section: Regulation Of Flowering Pathway Genes In the Transgenicmentioning
confidence: 88%